2017
DOI: 10.1039/c6cp07688b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of asymmetrical gemini surfactants

Abstract: The effect of variation in the length of surfactant hydrocarbon tail groups was tested in a series of dissymmetric gemini surfactants (N-alkyl N,N,N,N-tetramethyl-N-(6-pyren-6yl)-hexyl)propane-1,3-diammonium dibromide designated as CCCBr, with m = hexyl pyrene, and n = 8, 12, 14, 16, and 18. The aggregation properties of these surfactants have been investigated by means of H NMR, fluorescence spectroscopy, surface tension and electrical conductivity measurements. The critical micelle concentration (CMC) was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Surface activity of heterogeminis strongly depends on degree of the asymmetry. For pyrenebased dissymmetric gemini surfactants synthesized in five-step reactions ( Figure 16) [76], the Krafft temperatures increase with the increase of the alkyl chain length. Similarly, CMC values are much lower than those of their symmetrical counterparts.…”
Section: Application and Characterization Of Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface activity of heterogeminis strongly depends on degree of the asymmetry. For pyrenebased dissymmetric gemini surfactants synthesized in five-step reactions ( Figure 16) [76], the Krafft temperatures increase with the increase of the alkyl chain length. Similarly, CMC values are much lower than those of their symmetrical counterparts.…”
Section: Application and Characterization Of Surfactantsmentioning
confidence: 99%
“…The antimicrobial activity depends not only on the length of the substituent but also is dependent on the length of spacer [76,137,143,147,148]. In general, the longer the spacer, the better the antimicrobial activity ( Figure 26) [77].…”
Section: Biological Activity 61 Antimicrobial Activitymentioning
confidence: 99%
“…Besides the imidazolium family, other types of SAILs have also been investigated, namely ammonium‐, phosphonium‐, morpholinium‐, and guanidinium‐based SAILs . Brown et al .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the absence of the spacer group may confer relatively low flexibility to the molecules, with potential implications on the interfacial properties, namely, on micellization . In 2017, Muslim and co‐workers reported the synthesis and characterization of two groups of asymmetrical dicationic ILs based on ammonium cation. The first group consisted of SAILs with one hexyl pyrene tail and one alkyl chain, whereas the second group had two asymmetrical alkyl chains.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the surface/interface activity of gemini surfactants is orders of magnitude higher than that of single-chain surfactants. [6][7][8][9][10][11][12][13][14] The oil/water interfacial tension (IFT) reduction is the main mechanism of surfactant ooding. Thus, gemini surfactants have great potential for EOR application.…”
Section: Introductionmentioning
confidence: 99%